FAKTOR RISIKO LINGKUNGAN FISIK RUMAH DAN KARAKTERISTIK MASYARAKAT TERHADAP KEJADIAN PENYAKIT KUSTA DI KECAMATAN KERITANG KABUPATEN INDRAGRIRHILIR - Jadi Prasmadi; Aras Mulyadi; Zahtamal Zahtamal (Jurnal Ilmu Lingkungan, 2018)
From the results of the prevalence of leprosy on 10 houses of lepers in Keritang Sub-district as follows 7 houses lacking of ventilation, 8 homes lacking of lighting, 7 houses have high humidity, and 8 houses have dense housing, for the characteristics of the community 7 people work as farmers and have income under the Indragiri Hilir Regency Regional Minimum Wage. The purpose of the study was to analyze the risk factors of the physical environment of the house, the risk factors of community characteristics, the most dominant risk factors and describe the socio-economic effects of leprosy. The study was conducted from February to April 2018, the number of samples was 25 people and controls 50 people. The research population of all the keritang communities suffering from leprosy has been diagnosed by a doctor and recorded in the register of the City Health Center. The research instruments were questionnaires, observation sheets and stationery and roll meter measuring instruments, luxmeter and hygrometer. This study used a survey method with case-control design to determine the risk factors of the physical environment of the house and community characteristics associated with the incidence of leprosy in the Keritang District, Indragiri Hilir Regency. The results showed that there was an influence of 0.027 Pvelue ventilation (OR 3.6), 0.007 Pv (OR 5.1), Pv humidity 0.001 (OR 6.5), 0.041 Pv (OR 3.3), 0.018 Pv occupancy (OR 3.9), income of Pv 0.016 (OR 4.3). The dominant risk factors for air humidity are Exp (B) / OR of 5,487 and employment of 4,358. Socio-economic effects: 92.% are still working, 82.6% are still productive and 17.4% are not productive, 80% are not easy to get health services, 80% still have stigma or fear and 100% say it is still difficult to get married or accepted by society.